Mafhum Al Naskh min Mandhur Al Fiqh Al Maqashidiy: Dirasat wa Niqasy - Mubarrak, Husni; Munir, Badrul (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
This simple article discusses the concept of naskh and its division in Qur'anic studies. The study of naskh has become increasingly important, not only in ulumul Qur'an but also extending to other Shari'ah disciplines, including the science of ushul fiqh, which concentrates on the discovery of legal arguments and methods of istinbath Shari'ah law. This article argues for the importance of reviewing the study of naskh by placing maqashid scales as a parameter on the fulfillment of benefits and harms, especially with regard to the classification of naskh and the distribution of examples. The author uses the literature study method in this research by referring to motherbooks in classical ulumul Qur'an studies as well as various contemporary references, including recent scientific journal articles, in order to discuss the issue of the concept of naskh in the review of fiqh maqashid studies and debate the long-circulating shubhat views surrounding the study of naskh. The results of the study show that the division of the kinds of naskh by rasm and tilawah as narrated in 'ulumul Qur'an into three forms - according to the review of Fiqh Maqashid - is unacceptable, because it opens the door to doubt and even skepticism about the Book of Allah, therefore such a model of naskh division must be rejected to realize a greater and greater benefit in maintaining this religion and maintaining the sanctity and authenticity of the Qur'an.